(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the Microimplant-assisted Rapid Palatal Expansion (MARPE), considered an alternative to surgical interventions for disjunction of the midpalatal suture in adolescent patients and young adults with maxillary transverse deficiency. The stage of ossification of the midpalatal suture, bone quality and adequate activation protocols are factors that can influence the quantity and quality of the orthopedic separation. Methodology: This paper demonstrates the application of MARPE in an unfavorable case report, of an adult patient with total crossbite, in an advanced stage of fusion of the palatine and maxillary processes, with poverty in the posterior bone volume, in comparison with the same therapy in an adolescent at an earlier stage of sutural maturation. In both cases, after tomographic examinations and oral scanning, the installations and recommended activation protocol were performed. These were not sufficient in the case of the adult patient, and generated side effects that, to be overcome, required changes in activations and additional maneuvers. Results: The application of MARPE may require clinical versatility to adopt differentiated protocols in relation to chronological age, bone thickness and sutural ossification stage. Conclusion: In the end, new computer tomography scans and a clinical examination showed satisfactory results in both patients. In the unfavorable case, the opening of the midpalatal suture occurred at more modest levels, but it was sufficient to correct the posterior crossbite.